Genetic and morphological evidence for a new cryptic species of Ectinogonia (Coleoptera: Buprestidae) from central Chile - Anguita-Salinas, Simón; Barahona-Segovia, Rodrigo M.; Poulin, Elie; Zúñiga-Reinoso, Alvaro (Zootaxa, 2017)
The genus Ectinogonia Spinola, 1837 is a genus mainly found in Chile; it currently contains 17 species. Recent exploration in the Andes Mountain Range of the Bio Bio Region in Chile have resulted in the collection of specimens slightly different morphologically from all previously described species. The aim of this paper is to describe this new species of Ectinogonia using morphological and genetic evidence. To establish differences between species we described the external morphology and compared it to species that are morphologically similar (i.e. E. buqueti Spinola 1837 and E. intermedia Kerremans 1903). We also measured the genetic differences in COI sequences, constructing a distance matrix in which we compared it to species that are morphologically similar (E. buqueti and E. intermedia) and other species found in the same region (E. speciosa oscuripennis Moore 1994). We found that E. cryptica sp. n. differs from E. buqueti (which previously contained E. cryptica sp. n.) in pronotum and elytral patterns. The genetic distance matrix shows that E. cryptica sp. n. differs by 4.6% from all other Ectinogonia species compared, supporting the morphological evidence.